Mengendalikan perilaku polisi melalui kamera badan: Sebuah ulasan singkat - Panji Yugo Putranto (Jurnal Litbang Polri, 2022)
An adoption of body-worn cameras by police institutions would need a sufficient preliminary study. This article aims to provide a literature review for police managers in considering their decision to implement body-worn cameras on field officers. The use of body-worn cameras have yield mixed results from police institutions worldwide. Cameras, in theory, would serve as an accountability measure in making sure that procedures are being followed. On the other hand, the presence of a camera may limit discretionary action and slow down an officer’s decision-making. Evidences from previous research showed that BWCs promotes behavioral change, but their direct effectiveness in reducing public complaints remain arguable. It is then proposed that police institutions should carefully consider their policies regarding the implementation of BWCs due to their high cost and debatable e